Detailed seismic velocity of the incoming subducting sediments in the 2004 great Sumatra earthquake rupture zone from full waveform inversion of long offset seismic data. Issue 7 (1st April 2017) - Qin, Yanfang; Singh, Satish C.
Abstract: The nature of incoming sediments defines the locking mechanism on the megathrust, and the development and evolution of the accretionary wedge. Here we present results from seismic full waveform inversion of 12 km long offset seismic reflection data within the trench in the 2004 Sumatra earthquake rupture zone area that provide detailed quantitative information on the incoming oceanic sediments and the trench‐fill sediments. The thickness of sediments in this area is 3–4 km, and P wave velocity is as much as ~4.5 km/s just above the oceanic crust, suggesting the presence of silica‐rich highly compacted and lithified sediments leading to a strong coupling up to the subduction front. We also find an ~70–80 m thick low‐velocity layer, capped by a high‐velocity layer, at 0.8 km above the subducting plate. This low‐velocity layer, previously identified as high‐amplitude negative polarity reflection, could have porosity of up to 30% containing overpressured fluids, which could act as a protodécollement seaward from the accretionary prism and décollement beneath the forearc. This weak protodécollement combined with the high‐velocity indurated sediments above the basement possibly facilitated the rupture propagating up to the front during the 2004 earthquake and enhancing the tsunami. We also find another low‐velocity layer within the sediments that may act as a secondary décollement observed offshore central Sumatra, forming bivergent pop‐up structures and acting as a conveyer belt in preserving these pop‐up structures in the forearc region. Key Points: Elastic full waveform inversion is applied to long offset streamer seismic data that were acquired at North Sumatra subduction trench The inversion provides detailed P wave velocity information on the incoming oceanic sediments and the trench‐fill sediments There is a low‐velocity protodécollement layer above the highly compacted pelagic sediments, which could contribute to the 2004 tsunami